A network meta‐analysis of the effectiveness and safety of drugs for restless legs syndrome in dialysis patients. Issue 4 (28th September 2021) - Tang, Meng; Ge, Jie; Sun, Ke‐Xin; Cui, Bin; Guan, Yue; Wang, Jing‐Wen
Abstract: Objective: To evaluate the efficacy and safety of nine pharmacological interventions for restless legs syndrome (RLS) in dialysis patients. Methods: An electronic database was used to retrieve eligible trials from PubMed, Cochrane, Embase, and Web of Science. Stata 14.2 software was used to perform network meta‐analysis. The primary measure was the RLS score, and the secondary measure was used to evaluate the side effects of the drug. The surface under the cumulative ranking curve method was used to rank the merits of intervention measures. A comparison of the two interventions is shown on a league table. Results: Finally, nine randomized controlled trials (RCTs) with a total of 377 participants were included. From the results of the network meta‐analysis, all treatments ranked higher than placebo in terms of improving clinical symptoms, but only vitamin C (standardized mean difference [SMD] = −1.47 95% confidence interval [CI] −2.89, −0.05) showed significant differences compared with placebo. In terms of safety, there were no serious adverse reactions to any of the treatments compared to placebo. Conclusion: Currently, existing evidence suggests that vitamin C may be the most ideal drug to improve the symptoms of RLS in dialysis patients.